2015
DOI: 10.4236/ojgas.2015.57016
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Inflammatory Protein-1 Beta (MIP-1<i>β</i>) and Platelet Indices as Predictors of Spontaneous Bacterial Peritonitis<br> —MIP, MPV and PDW in SBP

Abstract: Background/Aims: The objective of this study is to measure macrophage inflammatory protein one beta (MIP-1β), mean platelet volume (MPV) and platelet distribution width (PDW) to evaluate their usefulness in the diagnosis of spontaneous bacterial peritonitis (SBP) in cirrhotic patients. Materials and Methods: This study comprised 41 cirrhotic patients with ascites. MPV, PDW and MIP-1β were measured in serum and ascitic fluid. Results: A significant increase MPV, PDW, C-reactive Protein (CRP) and white blood cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
7
6
0
Order By: Relevance
“…As regards acute inflammatory marker C reactive protein (CRP) in serum, the current study showed a significant increase in SBP versus none SBP group. This result matched with previous results 7,9,[12][13][14][15] .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…As regards acute inflammatory marker C reactive protein (CRP) in serum, the current study showed a significant increase in SBP versus none SBP group. This result matched with previous results 7,9,[12][13][14][15] .…”
Section: Discussionsupporting
confidence: 93%
“…In this study, there was a positive correlation with total leucocyte count, serum CRP and ascitic fluid LDH in the SBP group. However, Khorshed et al found a positive correlation between MIP-1β, mean platelet volume, platelet distribution width, and PMN in ascites 7 . The current study revealed a significant decrease in ascitic fluid MIP-1β after 48 hours of proper intravenous antibiotic administration.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations